Rebuilding Islamic Religious Education: Toward Meaningful Learning Through Teaching Innovation - Eprianto; Ari Koswara; Abdurrahmansyah; Nurlaila (Sustainable, 2026)
Islamic Religious Education (IRE) plays a crucial role in shaping students’ moral character and spiritual awareness. However, contemporary IRE remains dominated by teacher-centered instruction and rote memorization, limiting students’ ability to contextualize Islamic values. Despite ongoing reform discourses, a critical research gap persists: the absence of a systematic instructional framework that effectively bridges theological foundations with contemporary pedagogical, contextual, and digital realities. This study analyzes instructional design development in IRE through conceptual deconstruction to promote meaningful learning. The novelty of this research lies in proposing a theo-anthropocentric instructional framework that reconceptualizes IRE pedagogy by integrating student-centered strategies, contextual relevance, and digital technology. Employing qualitative library research, data from scholarly works (2020–2025) were synthesized using content and descriptive–analytical techniques. Findings reveal that traditional models overemphasize cognitive knowledge while neglecting affective and experiential dimensions. Consequently, IRE transformation requires innovative pedagogies and technological integration to connect religious teachings with authentic experiences. Ultimately, IRE must transcend mere knowledge transmission to cultivate meaningful learning that fosters moral responsibility, critical reflection, and spiritual growth in contemporary learners.